ISLAMIC RELIGIOUS EDUCATION IN THE FAMILY, DIGITAL PARENTING IN THE ERA OF GENERATION ALPHA STUDENT PERCEPTIONS OF PAI FTIK IAIN PONTIANAK - Heriansyah Heriansyah; Indri Astuti; Afandi Afandi (The Pontianak State Institute of Islamic Studies, 2023)
The focus of this research is how Islamic Religious Education in the Family, Digital Parenting in the Era of Generation Alpha. The problems that will be raised in this study are, First, the Perceptions of PAI FTIK IAIN Pontianak Students About the Importance of Islamic Religious Education in Families in Generation Alpha. Second, why do PAI FTIK IAIN Pontianak students view that digital parenting in families in Generation Alpha is important. Third, What are the Challenges of Islamic Religious Education in the Alpha Generation of Digital Parenting Families According to the Perceptions of PAI FTIK IAIN Pontianak Students.This type of research is descriptive qualitative by using a qualitative approach, the data sources are obtained from primary data and secondary data. Data collection techniques are observation, interviews and documentation. Data analysis in this study was carried out by means of inductive analysis. Results and Discussion, First According to the Perceptions of PAI FTIK IAIN Pontianak Students First About the Importance of Islamic Religious Education in Families in Generation Alpha It is very important to give, because it becomes the basis for children to act, speak and behave. Second, why do PAI FTIK IAIN Pontianak students view that digital parenting in families in Generation Alpha is important, because children born in the alpha generation are familiar with digital gadgets or devices so parents must know the parenting model for their children in everyday life. . alpha generation, so that children can act wisely and not cross the line in using the internet. Third, the Challenges of Islamic Religious Education in the Family, Digital Parenting in Generation Alpha According to Student Perceptions of PAI FTIK IAIN Pontianak Must be Understood; Children's needs, children's potential, play needs, socializing needs.Keywords: Islamic Religious Education, Digital Parenting, Generation Alpha, Student Perception